TURNING POSITION TERHADAP KEJADIAN DEKUBITUS PASIEN ICU DI RUMAH SAKIT: TINJAUAN LITERATUR - Stepani Rita Yuliana; Panji Putro Pamungkas (Jurnal Kesehatan, 2025)
Pressure ulcers are a common complication in patients with immobilisation in the Intensive Care Unit (ICU). One effective prevention strategy is the provision of turning positions or periodic changes in body position. This article aims to systematically review various studies evaluating the effect of turning positions on the incidence of pressure ulcers in ICU patients. The research method used was a systematic literature review of databases such as Google Scholar, Garuda, and PubMed using the keywords ‘pressure ulcers,’ ‘mobilisation,’ and ‘position changes.’ The selected articles were empirical journals published in the last 10 years, written in Indonesian or English, and relevant to the focus on pressure ulcer prevention. The selection process followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. From 50 identified articles, 10 were selected for analysis (7 empirical studies, 2 case studies, and 1 literature review). The most commonly used interventions were position changes every 2 hours, repositioning mobilisation, progressive mobilisation, and log roll techniques. All studies demonstrated a significant reduction in the risk and incidence of pressure ulcers, as evidenced by improved Braden or Norton scores and reduced pressure ulcer severity (p < 0.05). Based on these findings, mobilisation and position changes were proven effective as preventive interventions for pressure ulcers. Actions such as repositioning, lateral positioning, early mobilisation, and log roll should become standard nursing practice in ICUs and inpatient wards.